SECOND SIGHT : A PAUL CHRISTOPHER NOVEL - McCarry, Charles (London, : Arrow, 1991)
Onetime secret agent Paul Christopher, enjoying his retirement in Washington, D.C., is called back into service when U.S. agents throughout the Middle East are kidnapped and exposed to a dangerous drug by an unknown adversary.